Material virtue : ethics and the body in early China - Csikszentmihalyi, Mark (Sinica Leidensia, 2004)
An examination of both excavated and transmitted texts that link ethics and natural philosophy, Material Virtue narrates the history of a neglected tradition that argues virtue has physical presence in the body, and rewrites the formative period of Confucianism.